Effect of water‐absorbing nanospheres on antistatic property of isotactic polypropylene fibers. Issue 15 (6th March 2014) - Liu, Hongxing; Tang, Jianguo; Wang, Yao; Huang, Linjun; Wang, Yanxin; Jiao, Jiqing; Liu, Jixian; Xin, Zhichao; Belfiore, Laurence A.
ABSTRACT In this article, novel antistatic isotactic polypropylene (iPP) fibers were prepared through adding ternary polymer water‐absorbing nanospheres (TPWANs) into iPP melt in melt spinning process. The TPWANs were synthesized through emulsion copolymerization of styrene (St), butyl acrylate (BA), and sodium allylsulfonate (SAS). The characterization results of Fourier transform infrared spectrometer (FT‐IR) and 1H nuclear magnetic resonance (1H NMR) confirmed the ternary components in this copolymer. Transmission electron microscopy (TEM) images indicated the nanospherical shape of TPWANs with the characteristics of 80–90 nm size range of diameter and good dispersion in iPP fibers. The volume resistance of iPP fibers decreased by three orders from 1012 to 109 Ω cm when the 6 wt % TPWANs was added into iPP fibers, indicating that the blend fibers have good antistatic property. Most importantly, the nanospherical structure of TPWANs imparts both the compatibility and antistatic property into the blend iPP fibers. © 2014 Wiley Periodicals, Inc. J. Appl. Polym. Sci. 2014, 131, 40568.